2022
DOI: 10.1200/op.21.00430
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Exposure During the Intravenous Administration of Chemotherapeutic Drugs: An Analysis of Clinical Practice and a Literature Review

Abstract: PURPOSE: Injectable cytotoxics may be formulated with ethanol. This study sought to quantify the amount of ethanol exposure during chemotherapy infusions. MATERIALS AND METHODS: We first reviewed the antineoplastic drugs (Anatomical Therapeutic and Chemical code L01) and oncologic supportive care drugs (eg, antiemetics) currently available in France, to identify preparations containing ethanol. The amount of ethanol in the final chemotherapy preparation was calculated. Next, we performed a 2-year, single-cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Ethanol is a commonly used solvent to increase solubility when manufacturing anticancer drugs for injection. According to a recent study conducted by Hiver et al [ 11 ] on ethanol contained in anticancer drugs available in France, the content of ethanol contained in each anticancer drug was 91 to 400 mg/mL for docetaxel, 395 to 440 mg/mL for gemcitabine, 385 to 402 mg/mL for paclitaxel, and 241 to 248 mg/mL for etoposide, respectively. In addition, the analysis showed that 3,172 of the 63,613 chemotherapy preparations (4.99%) contained more than 3 g of ethanol [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ethanol is a commonly used solvent to increase solubility when manufacturing anticancer drugs for injection. According to a recent study conducted by Hiver et al [ 11 ] on ethanol contained in anticancer drugs available in France, the content of ethanol contained in each anticancer drug was 91 to 400 mg/mL for docetaxel, 395 to 440 mg/mL for gemcitabine, 385 to 402 mg/mL for paclitaxel, and 241 to 248 mg/mL for etoposide, respectively. In addition, the analysis showed that 3,172 of the 63,613 chemotherapy preparations (4.99%) contained more than 3 g of ethanol [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent study conducted by Hiver et al [ 11 ] on ethanol contained in anticancer drugs available in France, the content of ethanol contained in each anticancer drug was 91 to 400 mg/mL for docetaxel, 395 to 440 mg/mL for gemcitabine, 385 to 402 mg/mL for paclitaxel, and 241 to 248 mg/mL for etoposide, respectively. In addition, the analysis showed that 3,172 of the 63,613 chemotherapy preparations (4.99%) contained more than 3 g of ethanol [ 11 ]. Several previous studies have reported that the concentration of ethanol in the blood may increase, and ethanol-induced symptoms may occur after administering anticancer drug-containing ethanol to a patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation